Enantioselective C–H Alkylation of N-Arylbenzamides with Vinyl Ethers Catalyzed by an Iridium/Chiral Phosphoramidite–Olefin Complex - Murakami, Kotone; Sakamoto, Kana; Nishimura, Takahiro (Synthesis, 2021)
Chiral phosphoramidite–olefin hybrid ligands were found to be effective in the iridium-catalyzed asymmetric alkylation of N-arylbenzamides with vinyl ethers. The reaction is catalyzed by a hydroxoiridium catalyst coordinated with the hybrid ligand to give the corresponding products in high yields with high branch selectivity and enantioselectivity.
Keywords: enantioselectivity; iridium; benzamides; catalysis; C–H activation